TRANSMISSION OF Sclerotinia sclerotiorum FROM SOYBEAN SEED TO SEEDLINGS - de Carvalho, Cristiane; Forti, Victor Augusto; Bonfim Junior, Mauro Ferreira; Moraes, Maria Heloisa Duarte; Menten, JosÃ© OtÃ¡vio Machado (REVISTA DE AGRICULTURA, 2016)
Sclerotinia sclerotiorum causes disease in a wide range of plants and their seeds are an important vehicle of disease dissemination. The transmission of this fungus from seeds to seedlings is still understudied, thus, this paper evaluated the transmission of S. sclerotium from infected soybean seeds to seedlings. Soybean seeds were cultured in contact with pathogen colonies for 18 and 24h; 50% of each sample was submitted to asepsis. To evaluate the transmission, the percentage and speed of emergence of the seedlings was recorded, then the emerged seedlings with/or without symptoms were harvested, cut into two segments and incubated on agar-bromophenol to confirm S. sclerotium transmission.Â Results showed that a lower emergence percentage and speed was obtained after 24h inoculation without asepsis; the transmission of S. sclerotiorum therefore occurred from soybean seeds to symptomatic seedlings. Asymptomatic seedlings do not present the fungus, indicating there was no transmission.